Seasonal influence on the essential oil chemical composition of Hyptis crenata Pohl ex Benth.: a valuable plant from Marajó, Brazil - de Lima, Maria Nancy Norat; Santos, Paulo Vinicius Lima; Jerônimo, Lucas Botelho; Viana, Rian Martins; da Silva, Joyce Kelly; Setzer, William N.; Maia, José Guilherme S.; Figueiredo, Pablo Luis B. (Frontiers in Chemistry, 2024)
Introduction: Essential oils (EOs) from the Hyptis genus have been reported as bactericides and fungicides. However, the properties of these oils can be affected by climatic factors, as well as the collection period, which promotes changes in the chemical composition of the oil. In this context, this study aimed to evaluate the climatological influences on the chemical composition of the essential oil from the leaves of Hyptis crenata. Methods: The leaves were collected in Marajó island (Brazil) monthly for a year. The EOs were obtained by hydrodistillation and analyzed by Gas Chromatography coupled to Mass Spectrometry (GC-MS). Pearson’s correlation was used to evaluate the relationship between climatic parameters, content, and chemical composition of essential oil; multivariate analysis was used to evaluate the interrelationship between samples and their chemical constituents. Results and Discussion: The constituents with the highest contents (>2.0%) in essential oils during the studied period were 1,8-cineole (28.48% ± 4.32%), α-pinene (19.58% ± 2.29%), camphor (11.98% ± 2.54%), β-pinene (9.19% ± 1.47%), limonene (6.12% ± 3.15%), α-terpineol (2.42% ± 0.25%) and borneol (2.34% ± 0.48%). β-Pinene significantly correlated (p < 0.05) with precipitation and humidity. According to the chemometric tools, two groups were formed: chemical profile I, marked by 1,8 cineole, α-pinene, β-pinene, borneol, α-terpineol, and limonene, while group II (July) presented a chemical type characterized by camphor. It is understood that the species in question can be a reliable source of biologically active components during different climatic periods in the Amazon. The chemical variability could have significant implications for the pharmaceutical industry and traditional medicine.